2001
DOI: 10.1606/1044-3894.185
|View full text |Cite
|
Sign up to set email alerts
|

Tag-Team Parenting: Costs and Benefits of Utilizing Nonoverlapping Shift Work in Families with Young Children

Abstract: Qualitative data are analyzed in an attempt to further understand the costs and benefits of utilizing nonoverlapping shift work as a strategy for balancing and weaving work and family. In addition to saving on child care costs, this strategy appeals to many families with young children because it enables the parents to provide all of the child care themselves. Though many families cite difficulties with scheduling, most say that the negative effects are tolerable because this strategy allows them to provide fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 15 publications
3
44
0
Order By: Relevance
“…Alternatively, having flexibility may lead individuals to increase their work hours to the extent flexibility allows more porous boundaries between work and personal life (Kossek et al 2005). That night shift times provide less flexible start and end times than day or evening shifts suggests that the latter hold more promise for parents attempting to manage child care coverage with non-overlapping or tag-team shift work (Hattery 2001;Perrucci et al 2007;Presser 2003). Finally, local government employment diminishes access for both women and men.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…Alternatively, having flexibility may lead individuals to increase their work hours to the extent flexibility allows more porous boundaries between work and personal life (Kossek et al 2005). That night shift times provide less flexible start and end times than day or evening shifts suggests that the latter hold more promise for parents attempting to manage child care coverage with non-overlapping or tag-team shift work (Hattery 2001;Perrucci et al 2007;Presser 2003). Finally, local government employment diminishes access for both women and men.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 99%
“…However, it decidedly does not pertain simply or even primarily to the sharing of child care labor, which many authors who write about modern families do emphasize ͑Ehrensaft, 1987; Fish, New, & VanCleave, 1992;Hattery, 2001;Perry-Jenkins, Pierce, & Goldberg, 2004͒. For even in the multitude of families across the globe where fathers shoulder virtually none of the day-to-day care of their infants and young children, most men nonetheless do have a profound developmental influence in the lives of their children.…”
Section: What Is the Essence Of Coparenting?mentioning
confidence: 99%
“…In a qualitative study from the U.S.A., Hattery explored the costs and benefits of using non-overlapping shifts as a strategy for balancing and weaving work and family (Hattery, 2001). She found that the main reason given for choosing non-overlapping shifts was that it could save child care costs and that all child care could be provided by the parents.…”
Section: Shift Work As the Choicementioning
confidence: 99%